2004
DOI: 10.1080/027868290505279
|View full text |Cite
|
Sign up to set email alerts
|

Particle Collection Characteristics of a Prototype Electrostatic Precipitator (ESP) for a Differential TEOM System

Abstract: A differential tapered element oscillating microbalance (TEOM) system that includes an electrostatic precipitator (ESP) that is alternately switched on and off has been developed to improve the measurement of airborne particulate matter mass. Preliminary results showed that it has the potential to overcome the difficulties inherent in PM mass measurement and holds the promise of the measurement of PM mass as it exists in ambient air at ambient temperature. A critical aspect of this device is that the ESP total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…At all flow rates the lowest ESP collection efficiency was observed for particles between 100 nm and 300 nm in mobility diameter. Similar results were also observed in many experimental studies as reported in literature [ 19 - 21 ]. The electrostatic velocity of particles in any ESP is a combination of the number of charges acquired by the particles and the particle mobility.…”
Section: Resultssupporting
confidence: 92%
“…At all flow rates the lowest ESP collection efficiency was observed for particles between 100 nm and 300 nm in mobility diameter. Similar results were also observed in many experimental studies as reported in literature [ 19 - 21 ]. The electrostatic velocity of particles in any ESP is a combination of the number of charges acquired by the particles and the particle mobility.…”
Section: Resultssupporting
confidence: 92%
“…The results show the particles of submicron size had higher penetration than that of nanometer size. These results were similar to that reported by Yi et al (2004) and , who indicated that the most penetrating size was about 0.2 µm. It is likely that the electrical mobility was not enough to remove particles as low charging efficiency ).…”
Section: Esp Performancesupporting
confidence: 82%
“…An electrostatic precipitator (Meyer et al 2002;Yi et al 2004) is used in place of the chilled filter (R&P FDMS) to remove particles during the 6 minute reference purge cycle. Similar to the FDMS, during the purge cycle SVM is lost from the TX40 collection filter and measured as a negative mass.…”
Section: Randp Differential Teommentioning
confidence: 99%